2021
DOI: 10.1038/s41467-021-24115-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of social distancing and face mask use with risk of COVID-19

Abstract: Given the continued burden of COVID-19 worldwide, there is a high unmet need for data on the effect of social distancing and face mask use to mitigate the risk of COVID-19. We examined the association of community-level social distancing measures and individual face mask use with risk of predicted COVID-19 in a large prospective U.S. cohort study of 198,077 participants. Individuals living in communities with the greatest social distancing had a 31% lower risk of predicted COVID-19 compared with those living i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
91
3
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(105 citation statements)
references
References 44 publications
6
91
3
5
Order By: Relevance
“…Pseudovirus concentrations at a 2 m distance from the source were below the limit of detection (LoD) when no mask was worn, indicating the importance of commonly accepted social distancing (>1.8 m) as a low-cost and low-tech tool for curbing the spread of SARS-CoV-2. This finding is consistent with that of a large prospective U.S. cohort study of 198,077 participants, wherein individuals living in communities with the greatest social distancing were predicted to have a 31% lower risk of predicted COVID-19 than those living in communities with poor social distancing [8] . Hence, it is strongly recommended to use social distancing in all situations during the pandemic.…”
supporting
confidence: 90%
“…Pseudovirus concentrations at a 2 m distance from the source were below the limit of detection (LoD) when no mask was worn, indicating the importance of commonly accepted social distancing (>1.8 m) as a low-cost and low-tech tool for curbing the spread of SARS-CoV-2. This finding is consistent with that of a large prospective U.S. cohort study of 198,077 participants, wherein individuals living in communities with the greatest social distancing were predicted to have a 31% lower risk of predicted COVID-19 than those living in communities with poor social distancing [8] . Hence, it is strongly recommended to use social distancing in all situations during the pandemic.…”
supporting
confidence: 90%
“…It was noticed that long COVID-19 was significantly associated with male gender and student groups and not with the older age group. This is contrary to studies that reported an association between long COVID-19 and older age (≥40 years) [18] or female gender [22,25]. Older age was correlated with weaker immunity and hence higher susceptibility to long-term complications, while female gender was correlated with biological differences and the apparently higher tendency of females to reporting.…”
Section: Discussioncontrasting
confidence: 93%
“…Dental practitioners are generally considered well prepared in cross-infection control measures, including the use of personal protective equipment (PPE), which has contributed to reducing infection rates [17]. Community-based studies, on the other hand, estimated that facemask use was more effective in reducing the risk of COVID-19 infection than distancing [18]. In the context of dental clinical settings, distancing is not applicable, as dental practice is largely carried out in close proximity to the patient, with high possibility of exposure to aerosols [19].…”
Section: Discussionmentioning
confidence: 99%
“…Second, our relative avoidance bias measure does not differentiate between a tendency to avoid unmasked individuals and a tendency to approach mask-wearing individuals. However, the latter tendency would also not be optimal, because wearing a mask does not compensate for the increased risk of infection in close distance (Kwon et al, 2021 ; Li et al, 2021 ). Third, spontaneous approach-avoidance tendencies toward individuals wearing a face mask were assessed using a computerized reaction time task (AAT).…”
Section: Discussionmentioning
confidence: 99%